Magnetic mesoporous TiO2 microspheres for sustainable arsenate removal from acidic environments. Issue 9 (24th July 2018) - Zhao, Yujuan; Wang, Changyao; Wang, Shuai; Wang, Chun; Liu, Yupu; Al-Khalaf, Areej Abdulkareem; Hozzein, Wael N.; Duan, Linlin; Li, Wei; Zhao, Dongyuan
Abstract : Unique magnetic mesoporous TiO2 microspheres exhibit superior arsenate removal performance and high stability in acidic environments. Abstract : Carcinogenic arsenic pollution in ground water seriously threatens the health and lives of humans all over the world. It is highly desirable to fabricate new materials for sustainable arsenate removal with high capacities, stabilities and recyclabilities. In this study, we demonstrate that uniform magnetic core–shell structured Fe3 O4 @Resorcinol-Formaldehyde@mesoporous TiO2 microspheres (denoted Fe3 O4 @RF@mTiO2 ) can function as excellent adsorbents for the fast removal of arsenate (As V ) in acidic environments with very high efficiency. The mesoporous TiO2 outer shell (50 nm in thickness) endows them with a high surface area of 337 m 2 g −1 and a large pore volume of 0.42 cm 3 g −1, thus resulting in a fast adsorption rate (1.16 g mg −1 h −1 ) and a high adsorption capacity (up to 139 mg g −1 ) calculated using the Langmuir model at a pH of 3. The inner Fe3 O4 core (130 nm in diameter) makes separation facile from wastewater using a magnet. Moreover, the hydrophobic properties of the RF interlayer (10 nm in thickness) are increased after calcination at 200 °C, and this can protect the inner Fe3 O4 cores against etching from acid solutions over long cycles. In addition, the study of the As V adsorption mechanism on the core–shell mesoporous Fe3 O4 @RF@mTiO2 microspheres shows the existence of electrostatic forces and surface complexation interactions between arsenate and partially crystallized TiO2 . Benefiting from all of these advantages, the multilayer magnetic core–shell structured design is expected to be a promising nanomaterial for long-term wastewater treatment.